World Bank East Asia and Pacific Economic Update, April 2016 : Growing Challenges - World Bank (Washington, DC, 2016)
In the past 6 months, developing East Asia and Pacific has faced a challenging external environment, but growth has generally remained resilient. Over the next 3 years, growth is expected to ease modestly. China will continue its gradual shift to a more sustainable growth path. Some economies will be affected by low commodity prices and weaker external demand. This outlook is subject to elevated risks. Countries should prioritize monetary and fiscal policies that reduce their exposure to risks and strengthen market confidence. In China, there is a need to reduce leverage. In several countries, action is required to enhance transparency, strengthen accountability, and redefine the role of the state. Efforts to reduce barriers to trade should be redoubled, with a particular focus on non-tariff measures and regulatory barriers, including to trade in services. The region must increase its readiness to benefit from the digital revolution, and in particular develop the essential “analog complements” to digital technologies.